Medical Spending in Denmark1. (September 2016) - Christensen, Bent Jesper; Gørtz, Mette; Kallestrup‐Lamb, Malene
Abstract: Using full population longitudinal data from merged administrative registers for Denmark, we document that medical spending is highly concentrated in the population and is persistent through time at the individual level. In addition, we provide overviews of institutional details of the Danish health care system, aggregate trends in health care expenditures and the relevant register data. Nearly two‐thirds of expenditures are on hospitals and one‐fifth on long‐term care, with the remainder roughly equally split between primary care and prescription drugs. Health expenditures are higher for men than for women from ages 61 to 78, and otherwise higher for women. Between ages 50 and 80, hospital expenditures more than triple for men while more than doubling for women, and total health expenditures quadruple for men while tripling for women. The top 1 per cent of all spenders account for nearly one‐quarter of total spending in a given year, and averaging over three years only reduces this fraction to one‐fifth. The top 20 per cent of spenders in a given year are more likely to remain in that category two years later than not. The poorest fifth of the population aged 25 and above are responsible for more than twice as much spending on health as the richest, and this reverse social gradient is even stronger for long‐term care and is stronger among men than among women, especially in hospital expenses. Expenditures in the year (over the three years) before death are nearly 12 times (respectively nine times) higher than average, but nevertheless are only 11 per cent (respectively a quarter) of lifetime spending. Out‐of‐pocket expenses on prescription drugs only amount to 3 per cent of total health expenditures and are less concentrated than these.